Antimicrobial Synergy between Aminoglycosides and Licorice Extract in Listeria monocytogenes - Myungseo Park; Liz Horn; Victoria Lappi; Dave Boxrud; Craig Hedberg; Byeonghwa Jeon (Pathogens, 2022)
Listeria monocytogenes is a foodborne pathogen that can develop serious invasive infections. Among foodborne pathogens, L. monocytogenes exhibits the highest case fatality despite antibiotic treatment, suggesting the current therapy should be improved. Although ampicillin and gentamicin are used as a combination therapy to treat listeriosis, our results showed there is no synergy between the two antibiotics. We discovered that aqueous extract of licorice generated significant antimicrobial synergy when combined with aminoglycosides, such as gentamicin, in L. monocytogenes. In the presence of 1 mg/mL licorice extract, for instance, the minimum inhibitory concentration (MIC) of gentamicin was reduced by 32-fold. Moreover, antimicrobial synergy with licorice extract made gentamicin-resistant clinical isolates of L. monocytogenes susceptible to gentamicin. Given the common use of licorice as a food sweetener in Western countries and a herb in Oriental medicine, our findings suggest that licorice extract can be potentially used as an antibiotic adjuvant to improve the efficacy of antimicrobial treatment of listeriosis.